Formulation of Green Tea Spray Gel as Supportive Therapy for Diabetic Foot Infection - Priani, Sani Ega; Efrida, Delfiana Aura; Aryani, Ratih; Mulkiya, Kiki; Syafnir, Livia (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Diabetic foot infection (DFI) is a common complication of diabetes, most frequently caused by Staphylococcus aureus. Green tea contains antibacterial compounds and may serve as a potential supportive therapy for DFI. This study aimed to develop a spray gel formulation containing green tea ethanol extract and evaluate its antibacterial activity against S. aureus. The extract was obtained using 96% ethanol through the reflux method and subsequently tested for antibacterial activity using the agar well diffusion method. The extract was incorporated into a spray gel formulation with Viscolam MAC 10 as the gelling agent. The resulting spray gels were evaluated for their physical properties and antibacterial activity. Green tea extract demonstrated antibacterial activity against S. aureus with a minimum inhibitory concentration (MIC) of 0.1%. Furthermore, the ethanol extract was successfully formulated into a spray gel using 5% Viscolam MAC 10, meeting quality requirements in terms of organoleptic properties, pH, viscosity, spray pattern, spray weight, drying time, and adhesion time. Formulations containing 0.75% and 1% GTE exhibited potent antibacterial activity against S. aureus. In conclusion, a green tea–based spray gel formulation with good physical characteristics and potent antibacterial activity has been successfully developed.